Multi- response optimization of arc ion plated Cr coating on Zr alloy claddings based on Taguchi method and grey relational theory; Journal of Nuclear Materials; Vol. 625 - Cheng Hou; Jian Sun; Kashkarov E. B. Egor Borisovich; Junyan Wang; Zeng Lin; Fei Sun; Hailiang Ma (2026, 2026)
Title screen